2020
DOI: 10.1111/gcb.15007
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of forest gas exchange: Considerations derived from a tomographic perspective

Abstract: The global exchange of gas (CO2, H2O) and energy (sensible and latent heat) between forest ecosystems and the atmosphere is often assessed using remote sensing (RS) products. Although these products are essential in quantifying the spatial variability of forest–atmosphere exchanges, large uncertainties remain from a measurement bias towards top of canopy fluxes since optical RS data are not sensitive for the vertically integrated forest canopy. We hypothesize that a tomographic perspective opens new pathways t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Additionally, a larger leaf area index will generally lead to a lower stability of under the same soil moisture (Farah et al, 2004). In general, due to the instability of , the above assumption will cause a negative bias of 10 %-20 % in the estimation of daily ET (Delogu et al, 2012;Ryu et al, 2012;Van Niel et al, 2012). This can explain why the validation in this paper showed that the ET estimated using SEBAL was underestimated.…”
Section: Temporal Scaling-up Methodsmentioning
confidence: 78%
“…Additionally, a larger leaf area index will generally lead to a lower stability of under the same soil moisture (Farah et al, 2004). In general, due to the instability of , the above assumption will cause a negative bias of 10 %-20 % in the estimation of daily ET (Delogu et al, 2012;Ryu et al, 2012;Van Niel et al, 2012). This can explain why the validation in this paper showed that the ET estimated using SEBAL was underestimated.…”
Section: Temporal Scaling-up Methodsmentioning
confidence: 78%
“…Nevertheless, several limitations and assumptions must be considered when interpreting the results. Satellite‐based monitoring of drought only allows to evaluate state and changes of the upper tree crown (Damm et al, 2020), while possible damages happening lower in the canopy or even at stem level are not visible. Nevertheless, defoliation leads to translucency of the canopy crown and reflectance from the understory adds (unwanted) variation to the spectral signal (Barry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Velpuri et al (2013) used ET estimated using MOD16 and the Operational Simplified Surface Energy Balance (SSEBop) with a spatial resolution of 1 km × 1 km to match the footprint of the flux tower data 440 in the USA. Several studies have indicated that the footprint should be determined by the height of the observation instrument and the intensity of the turbulence (Damm et al, 2020;Schmid, 1994). It should be noted that the footprint of the flux tower data used in this study varied with the meteorological conditions.…”
Section: Errors In Flux Tower Measurementsmentioning
confidence: 96%